2017
DOI: 10.14740/wjon1033w
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Malignant Paraganglioma: A Case Report and Review of Literature

Abstract: Metastasis is a rare presentation of non-secretory paraganglioma. Consequently, there is no standard of care for the treatment of metastatic malignant paraganglioma. The most widely used chemotherapy regimen for non-resectable cases includes cyclophosphamide, vincristine, and dacarbazine (CVD). CVD has been previously studied with variable therapeutic response. However, yttrium-90 (Y90) radioembolization has not been previously studied in the treatment of hepatic metastasis in patients diagnosed with malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
11
0
4
Order By: Relevance
“…Several studies have demonstrated that measurement of urinary metanephrines allows for greater diagnostic sensitivity than measurement of serum metanephrines [ 1 ]. Histological studies are then performed for definitive diagnosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that measurement of urinary metanephrines allows for greater diagnostic sensitivity than measurement of serum metanephrines [ 1 ]. Histological studies are then performed for definitive diagnosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los sitios más comunes de diseminación metastásica pueden ser cercanos al tumor primario; aunque esto no siempre sucede, localizándose con mayor frecuencia en pared torácica anterior, pared abdominal, cabeza, cuero cabelludo, y ombligo [6][7][8][9] . En relación con el tipo tumoral presentado por nuestra paciente, los paragangliomas son tumores neuroendócrinos que derivan de células cromafines de la cresta neural y se originan en los ganglios espinales del sistema autónomo, los cuales se localizan desde la base del cráneo hasta la pelvis, pudiendo ser o no secretores de sustancias 3,12,13 . El paraganglioma metastásico cutáneo es infrecuente, pero en caso de ocurrir la localización más frecuente es en cabeza 3,4 .…”
Section: Discussionunclassified
“…Pueden tener actividad mitótica atípica, invasión intravascular y necrosis. Las MC en general no afectan epidermis y pueden tener un patrón histológico similar al primario que les dio origen 3,7,13 . La IHQ es un complemento de gran importancia en estos tumores puesto que es positiva para cromogranina, sinaptofisina y enolasa neuronal específica 3,4,7,10,13,14 .…”
Section: Discussionunclassified
“…Such patients can either be managed with chemotherapy or with radionuclide therapy such as 177 Lu labeled SSTR peptide analogs or with 131 I-meta-iodobenzylguanidine. [ 12 13 ] After our scan findings, this patient was planned for chemotherapy, because the laryngeal lesion, lung nodules, and metastatic cervical lymph nodes were not concentrating 99m Tc-HYNIC-TOC.…”
Section: Discussionmentioning
confidence: 99%